Evaluation of post-vaccination immunoglobulin G antibodies and T-cell immune response after inoculation with different types and doses of SARS-CoV-2 vaccines: A retrospective cohort study - Al-Rifai, Rami H.; Alhosani, Farida; Abuyadek, Rowan; Atef, Shereen; Donnelly, James G.; Leinberger-Jabari, Andrea; Ahmed, Luai A.; Altrabulsi, Basel; Alatoom, Adnan; Alsuwaidi, Ahmed R.; AbdelWareth, Laila (Frontiers in Medicine, 2023)
Objectives To explore variations in SARS-CoV-2 anti-spike (anti-S), anti-nucleocapsid (anti-N), and neutralizing immunoglobulin G (IgG) antibodies, and T-cell response by type and number of vaccine doses. Methods In a SARS-CoV-2–vaccinated population, we quantified the anti-S, anti-N, and neutralizing IgG antibody concentration and assessed T-cell response. The association between having ≥ median concentration of the three IgG antibodies and T-cell response by number and type of vaccines was quantified. Results We surveyed 952 male participants with a mean age of 35.5 years ± 8.4 standard deviation. Of participants, 1.4%, 0.9%, 20.2%, 75.2%, and 2.2% were never vaccinated, primed with only one dose, primed with two doses, boosted with only one dose, and boosted with two doses, respectively. All were polymerase chain reaction-negative to SARS-CoV-2. BBIBP-CorV was the most commonly used vaccine (92.1%), followed by rAd26-S+rAd5-S (1.5%), and BNT162b2 (0.3%). Seropositivity to anti-S, anti-N, and neutralizing IgG antibodies was detected in 99.7%, 99.9%, and 99.3% of the study participants, respectively. The T-cell response was detected in 38.2% of 925 study participants. Every additional vaccine dose was significantly associated with increased odds of having ≥ median concentration of anti-S (aOR, 1.34; 95%CI:1.02–1.76), anti-N (aOR, 1.35; 95%CI:1.03–1.75), neutralizing IgG antibodies (aOR, 1.29; 95%CI: 1.00–1.66), and with having a T-cell response (aOR, 1.48; 95%CI:1.12–1.95). Compared with boosting with only one dose, boosting with two doses was significantly associated with increased odds of having ≥ median concentration of anti-S (aOR, 13.8; 95% CI:1.78–106.5), neutralizing IgG antibodies (aOR, 13.2; 95% CI:1.71–101.9), and T-cell response (aOR, 7.22; 95%CI:1.99–26.5) although not with anti-N (aOR, 0.41; 95%CI:0.16–1.08). Compared with priming and subsequently boosting with BBIBP-CorV, all participants who were primed with BBIBP-CorV and subsequently boosted with BNT162b2 had ≥ median concentration of anti-S and neutralizing IgG antibodies and 14.6-time increased odds of having a T-cell response (aOR, 14.63; 95%CI:1.78–120.5). Conclusions Boosting with only one dose or with only BBIBP-CorV after priming with BBIBP-CorV was insufficient, whereas boosting with two doses, particularly boosting with the mRNA-based vaccine, was shown to be associated with having a high concentration of anti-S, anti-N, and neutralizing IgG antibodies and producing an efficient T-cell response.